Rights of redress on supply of goods under consumer protection Act 1999: the issue of halal logo - Naimat, Nasihah; Abu Bakar, Elistina (Secholian Publication, 2021)
Halal logo is designed to protect consumers from fraud and mislabelling. However, over the years, there has been a controversy surrounding the use of a false halal logo to attract Muslim consumers to buy certain goods. The act of unethical business practice to attract consumers to buy their goods have caused some misunderstanding among consumers regarding the halal status of such goods. Therefore, the law is the most important mechanism in protecting the rights and interests of consumers to claim compensation if their rights have been violated. Under the Consumer Protection Act (CPA) 1999, it puts a responsibility on suppliers and manufacturers to ensure that the goods supplied are the same as specified. However, the question arises as to the extent to which consumers have the right of redress under the CPA 1999 in the issue of supplying false halal logo goods. By using the content analysis method, this article aims to analyze the scope and provisions of the CPA 1999 that govern matters relating to the supply of goods. The discussion of this article reveals that Part VI and VII of the CPA 1999 contains several loopholes that must be addressed in order to provide better rights of redress to consumers on the issue of supplying false halal logo goods.